Epibiont community variation on two morphologically different hydroid colonies: Amphisbetia operculata and Plumularia setacea (Cnidaria, Hydrozoa) - Meretta, Pablo Ezequiel (2014)
Information on differential fouling abundance and seasonal variation of hydroid colonies is scant. These biological structures seem to be relevant for recruitment of other taxa. In this sense, the present study provides information about vagile and sessile organisms on two morphologically different hydroid colonies, Amphisbetia operculata and Plumularia setacea, during all four seasons. Both species are frequent components of the benthic rocky outcrop community of Mar del Plata (Argentina). A total of 49 epizoites on A. operculata and 44 on P. setacea, belonging to 12 divisions/phyla were identified. The main groups found on both colonies were bryozoans, crustaceans and molluscs. In both basibiont hydroids, epibiont species coverage, richness and composition changed between the studied seasons, but total colony height did not influence total coverage. Morphological differences between the two hydroid colonies determined coverage differences at two colony heights and the type of attached organisms that could be found on these colonies. Algae and filamentous invertebrates are very scarce in the studied community, and thus A. operculata and P. setacea appear as the unique and frequent arborescent structures multiplying the available substrata in the analysed outcrops. Thus, hydroid colonies might play an important role providing habitats for epibionts. Furthermore, the morphological differences between both hydroids may determine coverage difference and the kind of attached organisms found on these colonies.